Lens Thickness and Associated Factors among Age-Related Cataracts Patients in Chattogram, Bangladesh - Chowdhury, Prakash Kumar; Chowdhury, Purnashree; Chowdhury, Pradipta Narayan; Khan, Mohammad Altaf Uddin; Akter, Afroza (IAHS Medical Journal, 2023)
Background: Lens Thickness (LT) is one of the important parameters in ocular biometry. The observation of LT among cataract patients is of great importance from clinical and pathophysiological perspectives. The study aimed to investigate the relationship between the LT and lens density changes concerning age, types and densities of agerelated cataracts in a sample of the Bangladeshi population. Materials and methods: It is a prospective observational case control study. A total of 2066 (n = 2066) participants were included in the study from an Eye Hospital in Chattogram, Bangladesh. All participants underwent standard vision testing. LT was evaluated using the immersion technique with A-scan ultrasound. The types and density of cataracts were identified with a slit-lamp attached to a video camera. Cataract was classified morphologically into cortical, nuclear, and posterior sub-capsular types. Nuclear cataract was observed under oblique illumination, and retro-illumination was used to assess cortical and posterior sub-capsular cataracts. The density of the lens nucleus was graded as Emery and Little classification. Results: Ages of the study population ranged from 40-95 years, with a mean age of 62.76 ± 9.43 years. Of the participants, 937 (45.4%) were males and 1129 (54.6%) were females. The mean LT was 4.15±0.86mm. The LT was greater in older (³60 years) patients than in the younger (41-59 years) (4.21±0.85mm versus 4.01±0.86mm, p < 0.001). The mean LT in male and female patients were, respectively, 4.18±0.89mm and 4.12±0.84mm with any statistical significance (p<0.097). The mean LT was the highest in nuclear cataracts (4.79 ± 0.39mm), followed by cortical (3.9 ± 0.73mm) and posterior sub-capsular cataracts (4.16 ± 0.93mm). The relation between LT and the Grade of cataract was insignificant (p<0.078). Conclusion: In this large Bangladeshi age-related cataractous population, we found that thicker lenses are associated with older age and nuclear cataracts. IAHS Medical Journal Vol 5(2), Dec 2022; 58-61